ISLAM IDEOLOGI KAUM TERTINDAS: COUNTER HEGEMONY KAUM MARGINAL DAN MUSTADâAFÃN - Thahir, Lukman S. (Institut Agama Islam Negeri (IAIN) Palu, 2009)
Islam is perceived as being not only a new religion by some writers of history, but also as a liberating force. The teaching of Islamâthe main source of which is the Qurâanâcontains a lot of teaching on liberation the oppressed from the oppressors. The Qurâan even firmly expressesÂ that the Prophet Moses was sent to liberate the oppressed from despotic ruler (Pharaoh). In this context, Â Islam appears as anÂ ideology that can be employed to liberate the oppressed from the despotic power.Â Kata Kunci: Islam, ideologi, kaum tertindas, kaum marginal